الأخطاء في تعليم مهارة الكلام وحلها عند اللغة المرحلية بالمستوى الفونيمات فوق القطعية للطلاب في الفصل الثامن بمدرسة محمدية 4 المتوسطة سورابايا - Suniyah, Inti Fadah; Thohir, Muhammad (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
The difficulties in learning maharah kalam at the level of suprsegmental phonemes are found when students learn Arabic. Intonation errors, stress, and pausing. Therefore, this research was conducted to find out these mistakes and the solutions given by teacher in SMP Muhammadiyah 4 Surabaya. This research is a qualitative descriptive with the population of 8th grade student and the sampling is 8th grade C. Data collection techniques used in this research are using the method of observation, interview and questionnaire. Data analysis techniques used aredata reduction, data display, and data verification. The results showed: 1) errors in word stress were 49 errors; 2) errors in intonation were 30 errors; 3) errors at pauses were 55 errors. The solutions given by teacher with these mistakes were: 1) instructing students to repeat the dialogue to use the right intonation, stress, dan pause; 2) translating the text of theconversation and students writing the translation in their books, then the students will better understand the difference in meaning from the differences in intonation, stress, dan pause; 3) the teacher gives examples of the correct pronounciation of words according to the right intonation, stress, and pause.